Characterization, antimicrobial, and antioxidant potentialities of first-time isolated silver nanoparticles synthesizing protein secreted by Lysinibacillus sphaericus. (November 2022) - Liu, Pei; Zhao, Wen-Hao; Song, Yang-Ping; Wang, Qiang; Kan, Yi-Fan; Wang, Shi-Yan; Xia, Ji-Lin; Bilal, Muhammad; Zhu, Xiao-Yan; Wang, Zhong-Xing; Sun, Min; He, Shuai; et al.
Abstract: For the last few decades, the green synthesis of metal nanoparticles has been one of the most important areas due to its widespread application. The silver nanoparticles (AgNPs) biosynthesized using microorganism has gained widespread attention for various applications, mainly in nanobiotechnology and nanomedicine. Here, we introduced a first-time isolated protein and studied the synthesis mechanism and the biological activities of AgNPs. The synthesizing protein was separated by ammonium sulfate [(NH4 )2 SO4 ] separation and purified by ion-exchange chromatography, then subjected to MALDI-TOF sequencing and obtained the corresponding base sequence. The synthesizing protein was determined to be a hypothetical protein ( Lysinibacillus sphaericus ) with a molecular mass of approximately 115 kDa and 1083 amino acids. According to the structural domain functional analysis, the synthesizing protein were predicted, including 2 main domains, the surface-layer homology (SLH) domain and the Big_5 superfamily (Bacterial Ig-like domain). AgNPs are prepared by the protein, confirmed by Ultraviolet-visible (UV–vis) spectrophotometer, and characterized by Dynamic Light Scattering (DLS), Fourier Transform Infrared spectroscopy (FTIR) and Transmission Electron Microscopy (TEM). The nanoparticles were spherical with an average size of 40 nm. The AgNPs were lethal to Staphylococcus aureus ( S. aureus ) with a MIC of 200 μg/mL and MBC of 300 μg/mL, and to Bacillus subtilis (B. subtilis), Escherichia coli (E. coli) and Bacillus cereus (B. cereus) with MIC of 300 μg/mL and MBC of 400 μg/mL. The AgNPs were also tested for antioxidant activities by the scavenging activity of DPPH radicals and reducing power and were found to show better antioxidant capability than the standards. This research hopefully provides helpful explorations of green synthetic and biological applications of AgNPs. Graphical Abstract: ga1 Highlights: Introduction of a novel protein, synthesis mechanism and biological activities of AgNPs. Separation and purification of AgNPs-synthetic protein by chromatography. Characterization of AgNPs using an array of advanced techniques. Potential antifungal activity of synthesized nanoparticles against various pathogens.